Agricultural Extension Program Planning in Paddy Rice Planting Pattern Settings (Jurnal Sosial Ekonomi Pertanian, 2022)
The purpose of this study is to analyze the factors that influence the planning of agricultural extension programs on the setting of lowland rice cropping patterns, and analyze how much impact the agricultural extension program has on the regulation of lowland rice cropping patterns. The object of the research is the farmers who carry out the regulation of the paddy rice cropping pattern every planting season. This research was conducted in Gorontalo Utara Regency from April to July 2021. The research was conducted using the explanatory method, which explains the influence between research variables, namely variable X agricultural extension programs and variable Y setting rice cropping patterns. The research sample was determined using the stratified random sampling method, namely by stratifying the sub districts and villages whose farmers cultivate lowland rice according to the rice cropping pattern. By using the Slovin formula, the sample size of farmers is 79 people. The results showed that the implementation of agricultural extension programs in the regulation of paddy rice cropping patterns was influenced by factors, namely the source of extension information, the frequency of extension visits, and the availability of extension facilities and infrastructure. Meanwhile, the magnitude of the impact of agricultural extension programs on the regulation of lowland rice cropping patterns is 60.1%.AbstrakTujuan penelitian ini (1) menganalisis faktor-faktor yang mempengaruhi perencanaan  program penyuluhan pertanian pada pengaturan pola tanam padi sawah, dan (2) menganalisis seberapa besar dampak program penyuluhan pertanian pada pengaturan pola tanam padi sawah. Penelitian dilakukan dengan menggunakan metode survey yang menjelaskan pengaruh antar variabel penelitian, yaitu variabel X program penyuluhan pertanian dan variabel Y pengaturan pola tanam padi sawah. Penentuan sampel penelitian dilakukan dengan teknik stratified random sampling, yaitu dengan menstratifikasi kecamatan dan desa yang petaninya membudidayakan padi sawah sesuai dengan pola tanam padi. Dengan menggunakan rumus Slovin jumlah sampel petani adalah 79 orang. Hasil penelitian menunjukan bahwa perencanaan program penyuluhan pertanian pada pengaturan pola tanam padi sawah dipengaruhi oleh sumber informasi penyuluhan, frekwensi kunjungan penyuluh, serta ketersediaan sarana dan prasarana penyuluhan. Sedangkan besarnya dampak program penyuluhan pertanian pada pengaturan pola tanam padi sawah sebesar 60,1 %. Artinya 39.9 % dampak progran penyuluhan pada pengaturan pola tanam padi sawah dipengaruhi oleh fakor lain diluar penelitian ini.
Keywords: Agricultural extension programs, extension information, extension facilities, frequency of extension visits, rice planting pattern